An Examination of the Effect of Perceived Risk on Preparedness Behavior. (June 2013) - Bourque, Linda B.; Regan, Rotrease; Kelley, Melissa M.; Wood, Michele M.; Kano, Megumi; Mileti, Dennis S.
This article explores and specifies the impact of risk perception on household preparedness for terrorism based on a representative sample of households in the United States. This was done by constructing a path model, which included factors that both predict risk perception and others that mediate its effect on preparedness behaviors. An unweighted sample of the nation was randomly split to allow a path model to be developed on a calibration sample, confirmed on a cross-validation sample, and rerun on the full sample using Mplus. Analyses were conducted on the unweighted samples. Results led to the conclusion that risk perception does not have a significant direct effect on preparedness behavior and that its effect is largely meditated by knowledge, perceived efficacy, and milling behavior. The theoretical and practical implications of these findings are discussed and recommendations are offered for future research.